Use of Indonesian Language in Space Outside Media in City of Timika - Novaria Panggabean (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2020)
The strategic position of the Indonesian language for the Indonesian people is reflected in the third pledge of the Youth Pledge in 1928 which reads